Acid‐etching of zinc metal particles augments adsorption and removal of cashew allergens from extracts. (6th May 2018) - Li, Yichen; Bren‐Mattison, Yvette; Grimm, Casey C.; Mattison, Christopher P.
Abstract: Food allergens can cause severe reactions even in very small amounts, and accidental allergen exposure poses a serious threat. Methods that can be used to reduce or eliminate allergens are sorely needed in the food processing industry. The binding of cashew allergens to zinc particles was evaluated, and a process was developed to reduce cashew nut allergens from extracts using acid‐etched zinc particles. While no allergen binding was detected with untreated zinc particles, SDS‐PAGE, and immunoblot revealed that following acid treatment, recruitment, and adsorption of cashew allergens to zinc surfaces was increased. Trypsin digestion and LC‐MS/MS analysis of protein bound to zinc particles revealed the presence of Ana o 2 and Ana o 3 specific peptides. The results indicated that recruitment of cashew allergens, particularly Ana o 3, to zinc particles is enhanced due to the acid‐etching of the zinc surface. The findings suggest the use of acid‐etched metal surfaces, such as zinc, can be used to reduce cashew nut allergens from extracts. This simple procedure could be used in future processing steps to reduce or eliminate cashew nut allergens from extracts used in food preparation. Practical applications: Cashew allergens can cause severe reactions even in very minute amounts. Acid‐etched zinc particles were shown to reduce the allergen content of cashew nut extracts. The process developed here was particularly good at removing the small Ana o 3 allergen from cashew nut extracts, but also partially removed Ana o 1 and 2. Cashew allergen binding to zinc particles occurred following acid treatment, but was not detectable in the absence of acid treatment. Preparation of acid‐etched zinc particles could potentially be used in the peanut and tree nut butter industries to create hypoallergenic nut‐based spreads as alternatives to those that are currently commercially available.